Modern neurogenetic representations of MELAS syndrome. Clinical cases (the lecture) - A. V. Shatalin; E. V. Mukhina; A. S. Kotov; M. G. Amirkhanyan (Русский журнал детской неврологии)
This lecture with a description of clinical cases presents information on such a mitochondrial disease from the group of hereditary metabolic diseases, like MELAS syndrome (OMIM: 540000). The main manifestations of this progressive disease are stroke-like episodes and a specific form of encephalopathy, including epileptic seizures with the presence of a phenomenon of "ragged red fibers" and early dementia. Clinical cases, given in this lecture, supplement the piggy bank of genetically verified mitochondrial diseases leading to the development of polymorphic neurological disorders and characteristic neuroimaging picture, namely the appearance of polymorphic ischemic changes in the temporal, parietal or occipital regions of the brain, that do not correspond to the zones of the main vascular blood supply, as the basis for the formation of such focus is the phenomenon of mitochondrial angiopathy, and not thrombosis. The description of clinical cases reflects our own observations and the main steps in the diagnosis of this severe hereditary disease, taking into account of the latest neurogenetic representations. In addition to the data given in the clinical course of the disease, the results of the genetic interpretation of the MELAS syndrome are given; modern methods of diagnosis and therapy are considered.